Prevalence and Factors Associated with Iron Deficiency Among Children Aged 6 Months to 12 Years Attending the Sickle Cell Clinic at Kitete Hospital Tanzania. - Lubeja, Amos Charles (M.D) (Kabale University, 2024)
Background Iron deficiency is reported to occur in children with Sickle Cell Anaemia. The prevalence of iron deficiency in children with Sickle Cell Anemia is reported to range from 5.5% to 67.7%. The primary objective of this study was to ascertain the prevalence and factors associated with iron deficiency among children aged 6 months to 12 years attending the Sickle Cell Clinic at Kitete Regional Referral Hospital in Tabora, Tanzania. Methods: A cross-sectional study was conducted among children aged 6 months to 12 years diagnosed with Sickle Cell Anaemia by using Hb Electrophoresis and who were attending the Sickle Cell Clinic at Kitete Regional Referral Hospital in Tabora, Tanzania. Data were collected through a structured questionnaire, and blood samples were utilized to measure serum ferritin, complete blood count, and C-reactive protein. Stool samples were collected for Helicobacter pylori antigen testing, hookworm ova, and occult blood. Data were entered into Epidata 4.6 and analysed using STATA version 17.0. Bivariate analysis was initially conducted on variables, retaining those with p-value <0.2 for multivariate analysis using backward elimination. Factors with p<0.05 at multivariate analysis were considered independently associated with iron deficiency, explained using adjusted odds ratios with 95% confidence intervals. Results: Among the 199 children with Sickle Cell Anaemia, the mean age was 71.1 (SD 46.9) months, with the majority being males (57.3%). The prevalence of iron deficiency was 15.6% [95% CI: 11.03-21.12]. Factors independently associated with iron deficiency in children with Sickle Cell Anaemia included a positive stool test for hookworm [AOR 26.8: (95% CI 5.7-126.0] and xi positive stool antigen for H. pylori [AOR 2.7 (95% CI 1.01-7.40)]. However; these estimates were imprecise probably due to our small sample size. Conclusions and Recommendations: This study revealed that one in six children with Sickle Cell Anaemia has iron deficiency. The likelihood of iron deficiency was higher in children with hookworm infestation and Helicobacter pylori infection. It is recommended to screen children with Sickle Cell Anaemia for iron deficiency and H. pylori infection. Deworming is recommended for children with Sickle Cell Anaemia, and those with H. pylori infection should receive appropriate treatment as per guidelines. Future studies on iron deficiency in children with Sickle Cell Anaemia should consider testing serum hepcidin levels to identify candidates suitable for safe iron supplementation.